Challenges of administrative data linkages: experiences of Administrative Data Research Centre for England (ADRC-E) researchers - Hannah Morris; Silvia Lanati; Ruth Gilbert (International Journal of Population Data Science, 2018)
Background Linkage between administrative datasets routinely collected by government departments and other statutory bodies create rich resources for policy-relevant research. We describe how ADRC-E has achieved linkage between health and education data for England, and the challenges presented by this process.